Marmoset brain segmentation from deconvolved magnetic resonance images and estimated label maps. Issue 5 (25th June 2021) - Bazzi, Farah; Mescam, Muriel; Diab, Ahmad; Falou, Omar; Amoud, Hassan; Basarab, Adrian; Kouamé, Denis
Abstract : Purpose: The proposed method aims to create label maps that can be used for the segmentation of animal brain MR images without the need of a brain template. This is achieved by performing a joint deconvolution and segmentation of the brain MR images. Methods: It is based on modeling locally the image statistics using a generalized Gaussian distribution (GGD) and couples the deconvolved image and its corresponding labels map using the GGD‐Potts model. Because of the complexity of the resulting Bayesian estimators of the unknown model parameters, a Gibbs sampler is used to generate samples following the desired posterior probability. Results: The performance of the proposed algorithm is assessed on simulated and real MR images by the segmentation of enhanced marmoset brain images into its main compartments using the corresponding label maps created. Quantitative assessment showed that this method presents results that are comparable to those obtained with the classical method—registering the volumes to a brain template. Conclusion: The proposed method of using labels as prior information for brain segmentation provides a similar or a slightly better performance compared with the classical reference method based on a dedicated template.